The Vectorial incidence and quantitative determination of Aedes aegypti (Diptera: Culicidae) in the cooperativas Lomas de la Florida, Pablo Neruda and Parish Letamendi in the city of Guayaquil, Province of Guayas, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2014)
The vectorial incidence of Aedes aegypti at immature stages associated to breeding sites was analized. A total of 750 houses from three localities in the city of Guayaquil have been visited and recorded between january and march 2013; those are located at cooperativas Lomas de la Florida-norte, Pablo Neruda-sur, and Letamendi-centro Parish. The highest rate of infestation have been detected in those houses of cooperativa Pablo Neruda, having 12% they are considered as of emergency for operative control levels. This result is followed by a 6.8% found at the cooperativa Lomas de la Florida, and 6% of Letamendi Parish, those are considered as alarming signs for future events as displacement and vector proliferation. In relation to breeding places for mosquitoes as used and disused containers present at the inspected houses, it have been observed that Pablo Neruda has 21.2%, that is the highest rate in comparison to 10.8% of Lomas de la Florida, and 10% of Letamendi Parish, those are considered as an alarm and emergency response in case of an outbreak of dengue. Also it has been established that in the three studied localities the most common oviposition sites for Aedes aegypti are the reservoir tanks for daily use, these represented by 8.73%, and followed by buckets, these recorded as 3.56%. The 75% of samples have been identified as Aedes aegypti, the remaining 25% belongs to Culex sp.
Keywords: Aedes aegypti; hatcheries; Guayaquil; oviposition; reservoirs